IMPACT OF DEBT TO ASSET RATIO (DAR), DEBT TO EQUITY RATIO (DER), CAPITAL STRUCTURE (STM) TO RETURN ON EQUITY ( ROE) IN TEXTILE MILL PRODUCTS INDUSTRIAL COMPANY ARE REGISTERED ON THE BEI - EDWIN BUSTAMI; SYAMSURIZAL TAN; ZULKIFLI ZULKIFLI (Journal of Business Studies and Management Review, 2019)
This study aims to analyze the development / change of DAR, DER, STM, and ROE, Effect of DAR, DER, and STM on ROE both simultaneously and partially, the magnitude of the effect of DAR, DER, and STM on ROE both simultaneously and partially, as well as variables the most dominant one affects ROE. DAR, DER, STM simultaneously have a significant effect on ROE. While partially for the DAR variable no effect on ROE. for the DER variable it affects ROE. for STM variables it is known that the effect has an effect on ROE. The magnitude of the effect simultaneously from DAR, DER, STM to ROE is 0.94 or 94%. The magnitude of the effect of DAR on ROE is equal to 22.8%. The magnitude of the effect of DER on ROE is 74.9%. The magnitude of the effect of STM on ROE is 50%. DER variable is the variable that has the most dominant effect on ROE with a value of 74.9%.